2016 WSES guidelines on acute calculous cholecystitis. Issue 1 (December 2016) - Ansaloni, L.; Pisano, M.; Coccolini, F.; Peitzmann, A.; Fingerhut, A.; Catena, F.; Agresta, F.; Allegri, A.; Bailey, I.; Balogh, Z.; Bendinelli, C.; Biffl, W.; et al.
Abstract Acute calculus cholecystitis is a very common disease with several area of uncertainty. The World Society of Emergency Surgery developed extensive guidelines in order to cover grey areas. The diagnostic criteria, the antimicrobial therapy, the evaluation of associated common bile duct stones, the identification of "high risk" patients, the surgical timing, the type of surgery, and the alternatives to surgery are discussed. Moreover the algorithm is proposed: as soon as diagnosis is made and after the evaluation of choledocholitiasis risk, laparoscopic cholecystectomy should be offered to all patients exception of those with high risk of morbidity or mortality. These Guidelines must be considered as an adjunctive tool for decision but they are not substitute of the clinical judgement for the individual patient.